2023
DOI: 10.1001/jama.2022.24032
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Performance of US Health Systems

Abstract: ImportanceHealth systems play a central role in the delivery of health care, but relatively little is known about these organizations and their performance.ObjectiveTo (1) identify and describe health systems in the United States; (2) assess differences between physicians and hospitals in and outside of health systems; and (3) compare quality and cost of care delivered by physicians and hospitals in and outside of health systems.Evidence ReviewHealth systems were defined as groups of commonly owned or managed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…For better or worse, independent medical practices and solo community hospitals are disappearing as they are acquired by hospital-based health systems. In this issue of JAMA , Beaulieu et al provide a detailed review of the current (2018) prevalence and performance of the 580 health systems they identified in the US. They found that 84% of general acute care hospital beds and 40% of physicians were part of health systems.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…For better or worse, independent medical practices and solo community hospitals are disappearing as they are acquired by hospital-based health systems. In this issue of JAMA , Beaulieu et al provide a detailed review of the current (2018) prevalence and performance of the 580 health systems they identified in the US. They found that 84% of general acute care hospital beds and 40% of physicians were part of health systems.…”
supporting
confidence: 91%
“…Beaulieu et al had to make many decisions about how to identify systems and the physicians and patients attributed to systems, and how to measure and statistically analyze systems’ performance. Alternative decisions could have been made, which will provide impetus and material for important additional research.…”
supporting
confidence: 90%
See 3 more Smart Citations